Can AI Companies Sell Your Medical Data? A Deep Dive into Privacy, Law, and the De-Identification Loophole - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Can AI Companies Sell Your Medical Data? A Deep Dive into Privacy, Law, and the De-Identification Loophole The integration of Artificial Intelligence (A...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation